Surface expression and function of p75/AIRM-1 or CD33 in acute myeloid leukemias: Engagement of CD33 induces apoptosis of leukemic cells - Vitale, Chiara (The National Academy of Sciences, 2001)
p75/AIRM-1 is a recently identified inhibitory receptor expressed by natural killer and myeloid cells displaying high homology with CD33. Crosslinking of p75/AIRM-1 or CD33 has been shown to sharply inhibit the in vitro proliferation of both normal myeloid cells and chronic myeloid leukemias. In this study, we analyzed acute myeloid leukemic cells for the expression of p75/AIRM-1. p75/AIRM-1 marked the M5 (11/12) and M4 (2/2) but not the M1, M2, and M3 subtypes according to the French–American–British classification. Cell samples from 12 acute myeloid leukemias were cultured in the presence of granulocyte/macrophage colony-stimulating factor. Addition to these cultures of anti-CD33 antibody resulted in ≈70% inhibition of cell proliferation as assessed by [(3)H]thymidine uptake or by the recovery of viable cells. Anti-p75/AIRM-1 antibody exerted a strong inhibitory effect only in two cases characterized by a high in vitro proliferation rate. After crosslinking of CD33 (but not of p75/AIRM-1), leukemic cells bound Annexin V and displayed changes in their light-scattering properties and nucleosomal DNA fragmentation, thus providing evidence for the occurrence of apoptotic cell death. Remarkably, when anti-CD33 antibody was used in combination with concentrations of etoposide insufficient to induce apoptosis when used alone, a synergistic effect could be detected in the induction of leukemic cell death. These studies provide the rationale for new therapeutic approaches in myeloid leukemias by using both chemotherapy and apoptosis-inducing mAbs.